2017
DOI: 10.3389/fphar.2017.00461
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TGF-β Mediated SMAD Signaling for the Prevention of Fibrosis

Abstract: Fibrosis occurs when there is an imbalance in extracellular matrix (ECM) deposition and degradation. Excessive ECM deposition results in scarring and thickening of the affected tissue, and interferes with tissue and organ homeostasis – mimicking an exaggerated “wound healing” response. Many transforming growth factor-β (TGF-β) ligands are potent drivers of ECM deposition, and additionally, have a natural affinity for the ECM, creating a concentrated pool of pro-fibrotic factors at the site of injury. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
373
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(402 citation statements)
references
References 123 publications
9
373
1
Order By: Relevance
“…Since PPARγ ligands that bind to canonical binding site are also effective in BLM-induced fibrosis (Wu et al, 2009;Wei et al, 2014), we can assume that, due to the versatile nature of the LBP of PPARγ, PPARγ-ms (partial agonist) are also effective at preventing inflammation and fibrosis. It has been previously shown that the canonical pathway activated by TGFβ drives the phosphorylation of SMADs that is upstream of the fibrogenic process (Walton et al, 2017). Our results show that VCE-004.3 reduces TGFβ-induced SMAD2/3 transcriptional activation and collagen synthesis but does not affect SMAD2/3 phosphorylation.…”
Section: Figuresupporting
confidence: 54%
See 1 more Smart Citation
“…Since PPARγ ligands that bind to canonical binding site are also effective in BLM-induced fibrosis (Wu et al, 2009;Wei et al, 2014), we can assume that, due to the versatile nature of the LBP of PPARγ, PPARγ-ms (partial agonist) are also effective at preventing inflammation and fibrosis. It has been previously shown that the canonical pathway activated by TGFβ drives the phosphorylation of SMADs that is upstream of the fibrogenic process (Walton et al, 2017). Our results show that VCE-004.3 reduces TGFβ-induced SMAD2/3 transcriptional activation and collagen synthesis but does not affect SMAD2/3 phosphorylation.…”
Section: Figuresupporting
confidence: 54%
“…It has been previously shown that the canonical pathway activated by TGFβ drives the phosphorylation of SMADs that is upstream of the fibrogenic process (Walton et al ., ). Our results show that VCE‐004.3 reduces TGFβ‐induced SMAD2/3 transcriptional activation and collagen synthesis but does not affect SMAD2/3 phosphorylation.…”
Section: Discussionmentioning
confidence: 97%
“…In aged muscles, excessive TGF‐β1 is produced, inducing unusually high levels of TGF‐β1/p‐Smad3 in resident satellite cells and impairing their regenerative capacity . Therefore, the inhibition of TGF‐β1 signalling has been investigated as a treatment option for muscle‐wasting disorders . For example, the inhibition of TGF‐β1 signalling by losartan treatment had dramatically beneficial effects on sarcopenic muscle by improving the regeneration after injury .…”
Section: Discussionmentioning
confidence: 99%
“…The sequential transition of three post‐traumatic repair phases mentioned above is pivotal in the HSs formation. In the fibrotic and antifibrotic events of wound healing, the imbalance between profibrotic growth factors and antifibrotic factors results in abnormal deposition of ECM showing HSs . To balance the two processes, an agent which binded to several targets is more refined.…”
Section: Biotherapy Aimed At Main Cytokines and Protein Involved In Hssmentioning
confidence: 99%
“…In the fibrotic and antifibrotic events of wound healing, the imbalance between profibrotic growth factors and antifibrotic factors results in abnormal deposition of ECM showing HSs. 168 To balance the two processes, an agent which binded to several targets is more refined. One typical example is decorin, a small leucine-rich proteoglycan, 169 which exists in the interstitial matrix of the dermis and combines with collagen fibrils preferentially, 170 and then setting their assembly.…”
Section: Biotherapy Aimed At Main Cytokines and Protein Involved Inmentioning
confidence: 99%